(untitled) (Contemporary Mathematics, 2025)
The present study introduce a regularization scheme yielding divergent free exact solutions to the classical field equations underlying the muon self-interaction. Exact results for the self-energy and anomalous g-factor of the muon and upper bound on the sum of the muon and electron neutrinos rest masses are reported. Yukawa cut-offs with unique screening constants regularizing the electromagnetic field inherent to the self-interacting muon are presented. Equations of motion and a transcendental equation satisfied by the muon anomalous g-factor are derived, with solution aµ = 0.001165920530996(3) matching the most recent experimental value found in the literature to 60 ppt showing an excellent agreement.